ICT Implementation In English Class In Globe School 1 Batam: Students’ And Teachers’ Perception - Gabriela Micheline Slikker; Gabriella Jap; Leil Badrah Zaki (Miftahul Ulum, 2024)
It's interesting to see how students are becoming more versatile and utilizing technology for learning. It will be used by students in the twenty-first century to satisfy ISTE standards and provide solutions for teachers who are still struggling to figure out how to adequately integrate technology to fulfill the standards' requirements for instructors. This study sought to understand how teachers and students experienced about using ICT in English classes at Globe 1 Batam. The school has active and ready-to-use ICT resources, but it's possible that the English teacher lacks sufficient expertise in promoting ICT in the classroom. The study employed a mixed-method research design and the ASSURE model. A total of 24 students 13 from the 9th grade and 11 from the 12th grade as well as teacher A, the English teacher for junior and senior high school, participated in this study. Four students were interviewed, and a questionnaire was completed by the team. Students demonstrate strong ICT proficiency, but teachers continue to feel that they're lacking. The results of the questionnaire indicate that the students are tech-savvy, which implies the teacher has potential. As a result, in order to assist the teacher in meeting the ISTE standards for educators, the team intends to facilitate her work by creating a video tutorial. This will enable the teacher to create her own assignments using Google Docs or other collaborative tools in the future.